The viscosity of atmospherically relevant organic particles - Jonathan P. Reid (Nature Portfolio, 2018)
The phase state of organic particles in the atmosphere has important consequences for the impact of aerosols on climate, visibility, air quality and health. Here, the authors review the evidence for the formation of amorphous glassy particles and the methods for determining aerosol particle viscosity.